Potential therapeutic applications of muscle-derived mesenchymal stem and progenitor cells - Jackson, Wesley M (2010)
IMPORTANCE OF THE FIELD: Mesenchymal adult stem cells have properties that make them attractive for use in tissue engineering and regenerative medicine. They are inherently plastic, enabling them to differentiate along different lineages, and promote wound healing and regeneration of surrounding tissues by modulating immune and inflammatory responses, promoting angiogenesis and secreting other trophic factors. Unlike embryonic stem cells, clinical uses of mesenchymal stem cells are not encumbered by ethical considerations or legal restrictions. AREAS COVERED IN THIS REVIEW: We discuss skeletal muscle as a source of mesenchymal stem and progenitor cells by reviewing their biology and current applications in tissue engineering and regenerative medicine. This paper covers literature from the last 5 – 10 years. WHAT THE READER WILL GAIN: Skeletal muscle is a plentiful source of mesenchymal stem and progenitor cells. This tissue may be obtained via routine biopsy or collection after surgical debridement. We describe the biology of these cells and provide an overview of therapeutic applications currently being developed to take advantage of their regenerative properties. TAKE HOME MESSAGE: There is potential for stem and progenitor cells derived from skeletal muscle to be incorporated in clinical interventions, either as a cellular therapy to modify the natural history of disease or as a component of engineered tissue constructs that can replace diseased or damaged tissues.